Mapping and assessing the multifunctional demand for agricultural land based on the “P-E-F” framework: A case study of Hangzhou City, China - Qian Yu; Shan He; Chenxia Hu; Shixue You; Lin Lin; Yue Su; Congmou Zhu; Chenhe Zhou (Ecological Indicators)
Assessing the demand for multifunctions of agricultural land (MAL) at a fine scale is critical for rationally optimizing the allocation of agricultural resources. However, the methodology for quantifying MAL demand is still exploratory and lacks a comprehensive evaluation system. This study thus proposed the “P-E-F” framework by integrating multi-source datasets (e.g., social network and remote sensing) in Hangzhou, China. Firstly, the MAL demand maps were drawn based on the “P-E-F” framework. Secondly, a multiscale analysis was conducted based on the MAL demand maps and their hotspot maps. Finally, we comprehensively analyzed the demand variations among land use types and agricultural functions to explore more precise information. The key findings are that 1) despite high MAL demand was generally concentrated near the downtown, some remote rural areas were also characterized by significant demand for cultural function; 2) compared to that of ecological and cultural functions, the production demand was less scale-dependent with a more aggregated distribution pattern; 3) agricultural land with compounding demand was clustered in the plains adjacent to cities, and hotspots of MAL demand in remote mountains were less frequently observed; 4) demand level for paddy field was outstanding among other agricultural land use types. We argue that regionally differentiated utilization and management of agricultural land are necessary from a sustainable development perspective. This study provides a new insight into the MAL demand assessment and can provide reference suggestions for the utilization, management, and planning of agricultural land.